Cohort study with 4‐year follow‐up of myopia and refractive parameters in primary schoolchildren in Baoshan District, Shanghai. (16th April 2018) - Ma, Yingyan; Zou, Haidong; Lin, Senlin; Xu, Xun; Zhao, Rong; Lu, Lina; Zhao, Huijuan; Li, Qiangqiang; Wang, Ling; Zhu, Jianfeng; He, Xiangui
Abstract: Importance: Cohort studies could not only reveal associations between change of refractive components and onset/progression of myopia, but also risk factors, which is important for understanding mechanism and providing strategies. Background: Prevalence of myopia is high in Shanghai, being reported to be 52.2% in children aged 10 years old. Design: Cohort study. Participants: A total of 1856 students from six randomly selected primary schools in Baoshan District, Shanghai. Methods: Children underwent comprehensive ocular measurement, including axial length (AL), corneal curvature radius and cycloplegic auto‐refraction. Questionnaires about eye usage time were collected. Grade 1 students were followed for 4 years, and grade 2 and 3 students for 2 years. Main Outcome Measures: (i) Change of spherical equivalent (SE) and AL and (ii) risk factors for progression and incidence of myopia. Results: The average 2‐year progress of SE was 0.91D, 0.91D and 1.11D for grade 1, 2 and 3, respectively, and the average elongation of AL was 0.70 mm, 0.64 mm and 0.71 mm, respectively. Only parental myopia, but not near work time, near work diopter time, outdoor activity time or attending tutoring classes, was associated with myopia incidence and progression in the present population. Using baseline SE could be a simple and effective indicator for myopia prediction. Conclusions and Relevance: Incidence and progression of myopia is relatively high in schoolchildren in Shanghai compared with children of Western countries, East Asia and other parts of China. Effective strategies to control myopia prevalence are in urgent need.